Erdoğan's comprehensive religious policy: management of the religious realm in Turkey - Çevik, Salim (SWP comment, 2019)
Tayyip Erdoğan’s management of the religious realm in Turkey relies on three different but complementary components: i) using state institutions and resources to define and control the religious discourse and life, ii) incorporating religious communities and organisations into the party and state institutions, and iii) forming new religious organisations and communities through family-controlled religious foundations (vakıf).